Caring touch as communication in intensive care nursing: a qualitative study - Lise Sandnes; Lisbeth Uhrenfeldt (International Journal of Qualitative Studies on Health & Well-Being)
Purpose This article describes intensive care nurses` experiences of using communicative caring touch as stroking the patient`s cheek or holding his hand. Our research question: “What do intensive care nurses communicate through caring touch?” Methods In this qualitative hermeneutically based study data from two intensive care units at Norwegian hospitals are analysed. Eight specialist nurses shared experiences through individual, semi-structured interviews. Results The main theme, Communicating safety and presence has four sub-themes: Amplified presence, Communicating security, trust and care, Creating and confirming relationships and Communicating openness to a deeper conversation. Communicative caring touch is offered from the nurse due to the patient`s needs. Caring touch communicates person-centred care, invites to relationship while respecting the patient’s dignity as a fellow human being. Caring touch conveys a human initiative in the highly technology environment. Conclusion Caring touch is the silent way to communicate care, hope, strength and humanity to critical sick patients. This article provides evidence for a common, but poorly described phenomenon in intensive care nursing.